Political Strategy of the K.H. Hosamuddin in Developing a Civilized Community in the Timur Daya - Rosy, Fathor; Ikmal, Moh.; Basri, Hasan (SAINTIS Publishing, 2024)
The research highlights the inclusive approach implemented by K.H. Hosamuddin, which respects local traditions while promoting positive change through community involvement in decision-making. By emphasizing the importance of good social relationships and effective communication, he successfully strengthened social networks within the community. Additionally, local wisdom became a primary focus in development programs, enhancing social and educational effectiveness. Although there is no quantitative data showing a significant increase in income, the positive impact of his leadership is reflected in the more productive and future-oriented behavior of the community. This journal provides insights and recommendations for leaders and community figures in efforts to create an inclusive and competitive society in the modern era, while also affirming K.H. Hosamuddin's success in fostering an environment that supports social and spiritual growth